Marlow’s Gaze in Lord Jim by Joseph Conrad: Between Light and Shadows - Sokołowska, Katarzyna (Studia Anglica Posnaniensia, 2019)
In Lord Jim Marlow functions not only as a narrator who spins the yarn about the morally problematic case of the young sailor, but also as an interpreter who struggles to register impressions as faithfully as possible thus translating the visual into the discursive. Marlow’s double function establishes the novel as a text about the search to understand and to acquire reliable knowledge about Jim and his dilemma. Levin’s distinction of the two styles of vision, the assertoric gaze and the aletheic gaze, offers a neat conceptualization for Marlow’s visual practices which affect his interpretation of Jim. Levin defines the assertoric gaze as a fixed stare which involves the hegemony of a single standpoint, whereas the aletheic gaze, decentred and subversive, cherishes ambiguity and tends to roam about to accommodate multiple points of view. Levin relates this distinction to the two concepts of truth that Heidegger examines in his critique of the metaphysics of presence: truth as proposition, correspondence, or correctness and truth as aletheia or unconcealment as well as the two types of discourse, the hermeneutical discourse of poetizing and the discourse of statements. If Plato and Descartes defined truth and knowledge in terms of a total visibility, Heidegger insists that the path to truth involves confronting shadows and recognizing that they are necessary for the disclosure of being. Within this philosophical framework it is possible to reassess both Marlow’s failure to form an unequivocal explanation of Jim and his growing epistemological scepticism as a departure from the correspondence theory of truth. The encounter with Jim brings Marlow to interrogate his own strategies of grasping the truth and subverts the focus on light as its visual equivalent.